An in vivo study on using capsaicin as a potential analgesic for post-operative pain in rat paws - Bañas, Catherine B.
Capsaicin, an essential element in chili peppers, has been used in many topical analgesic agents. This study aimed to determine that potential analgesic effect of capsaicin if used intraoperatively for management of post-operative pain. Sixteen rats were randomly divided into groups of four and underwent plantar incision of the right hind paw. The first group served as control and underwent a sham procedure consisting of incision without capsaicin application. The second third and fourth groups recevied three different capsaicin concentrations (0.025%, 0.075%, 0.25%) respectively. Analgesia was assessed using two tests: heat and behavioral tests, which are used to assess the level of pain in laboratory rats after induction to surgical pain. These tests were done at different time intervals (after 2,6,24 and 48 hours). Nociceptive scores obtained during observations for each group of rats were averaged and compared across groups using two-ways ANOVA followed by LSD Post Hoc test. Based on the statistical results, rats treated with capsaicin had lower nociceptive scores than control rats. The minimum effective dose of capsaicin was found to be at 0.025%. It was also determined that the effect of capsaicin becomes more profound as time lapses, thus it may serve as an effective analgesic for postoperative pain.